Hot Formation for Improved Low Temperature Cycling of Anode-Free Lithium Metal Batteries. Issue 14 (3rd October 2019) - Genovese, Matthew; Louli, A. J.; Weber, Rochelle; Martin, Cameron; Taskovic, T.; Dahn, J. R.
Abstract : A new "hot formation" protocol is proposed to improve lower temperature cycling of lithium metal batteries. The cycling stability of anode-free pouch cells under low pressure (75 kPa) is shown to decline significantly as the cycling temperature is decreased from 40°C to 20°C. At low pressure and 40°C the initial morphology of the lithium anode is dense and columnar, far superior to that plated at 20°C. For "hot formation" two initial 40°C cycles (C/10 charge C/2 discharge) are conducted prior to extended low temperature (20°C) cycling. These two initial cycles have a surprisingly large impact; capacity retention to 80% is increased from only 18 cycles without hot formation to 60 cycles with hot formation at low pressure. When the applied pressure is increased to 1200 kPa, the hot formation (20°C cycling) cells show 85% capacity retention at 100 cycles. The benefits established during these two initial formation cycles are apparently carried forward to improve the longer term performance of lithium metal cells tested at room temperature.